Infection processes and pathogenesis mechanism of Fusarium proliferatum in Bakanae disease - Quazi, Shireen Akhter Jahan (2014)
Bakanae disease caused by Fusarium (F.) species (spp.) was first reported to have a significant effect on Malaysian rice varieties in 1985 from the rice growing areas of Kedah, Kelantan and Perak. A total of five Fusarium spp. i.e. F.fujikuroi, F. proliferatum, F. sacchari, F. subglutinans and F. verticillioides were isolated and found to be associated with Bakanae disease in Malaysia. It was essential to identify the causal agent using morphological characteristics along with molecular techniques. There was little information on the infection processes and mechanisms of pathogenesis of Fusarium species in relation to development and symptoms expression of Bakanae disease in infected plants. Gibberellic acid (GA3) produced by the causal pathogen has been identified to be responsible for internode elongation, but a number of secondary metabolites produced by the causal pathogen in relation to disease development and symptoms expression were still unknown. Therefore, the aims of this research were to identify the causal Fusarium species in Selangor rice growing areas, to establish the role of phytohormonal imbalances and metabolites production by the fungus and pathogenesis-related (PR) protein activities in relation to disease symptoms expression in infected plants and to evaluate the symptoms expression analysis of Bakanae disease by pre-seed treatment with pure (synthetic) phytohormones and metabolites in susceptible rice variety MR 211. A total of 12 isolates from Tanjung Karang and from Sekinchan areas were obtained. All isolates were identified as Fusarium proliferatum by PCR with Pro1/2 primer and further confirmed by sequencing (Acc. JQ807850) in both directions. Seed inoculation was found to be the most suitable method compared to soil inoculation for pathogenicity test. SEM micrographs showedconidia of F. proliferatum germinated on seed surface of susceptible variety MR 211, 24 h after inoculation followed by colonization and symptoms initiation after 5 days after inoculation. Based on the varietal screening, MR 211 was identified as susceptible, whereas G-27 was moderately resistant and BR3 was resistant. In phytohormone analysis, highest up-regulation of IAA (94.1%) and a marginal percentage of GA3 (9.35%) occurred mostly in leaf tissues, whereas they were down regulated in root tissues (GA3 = -37.61%; IAA= -16.32%) and in the stem (GA3 = -29.75%; IAA= -39.21%) of infected susceptible variety MR 211 after 7 days of inoculation at a disease score of 1 (stunted plant with yellowing leaves). This indicates that up- and down regulation of phytohormones was associated with the expressed symptoms in elongation and the stunting effect coincides with chlorosis of leaves. In disease score 3 (abnormal elongated internodes with chlorotic or brownish leaves), the up-regulation of all analyzed phytohormones were observed to be high in stem tissues of susceptible variety MR 211 with GA3 = 77.46%, IAA = 87.38% and ABA = 98.55% compared to leaf and root tissues. In infected plants with disease score 5 (leaf and stem browning with elongated internodes, fungal mass seen on the infected plants or dead plant), the amounts of GA3 and IAA were down-regulated in susceptible MR 211 and this down regulation was reflected in the growth and development of leaves and roots and resultant senescence. Among the metabolites evaluated, moniliformin (MON) and fusaric acid (FA) were found to be associated with symptoms development and expression in susceptible variety MR 211. MON was found at disease score 3 (83.67 ng/g) and at disease score 5 (112.81 ng/g) in infected MR 211 plants. FA was found at all three disease score levels in infected susceptible MR 211 plants, but higher amounts were observed at disease score 1 (354.41 μg/g) and at disease score 5 (372.38 μg/g). No MON or FA was detected in resistant BR3 plant samples. The association of phytohormone GA3 and secondary metabolites FA and MON in relation to Bakanae symptoms expression were further confirmed when seeds of susceptible variety MR 211 were treated with synthetic GA3 phytohormone and synthetic FA and MON metabolites in the glasshouse. It was observed that GA3 was responsible for plant height elongation and leaf chlorosis, whereas FA was associated with plant height retardation, root growth retardation and chlorosis of leaves, and moniliformin was found to be associated with leaf and stem browning, crown rot and root necrosis in susceptible variety MR 211. Among the PR-proteins chitinase activity was found to be more prominent in the disease susceptibility/resistance mechanism against F. proliferatum than β-1, 3 glucanase activities. Chitinase activity increased from disease score 1 to disease score 5 in resistant variety BR3, whereas no activity was observed in susceptible variety MR 211. This is the first report that F. proliferatum is the pathogen causing Bakanae disease in rice plants and that metabolites FA and MON along with phytohormone GA3 produced by F. proliferatum in diseased plants are associated with a variety of disease symptoms expression.